A study on the stability of the led gain monitoring system for the CMS-HF PMTs during 2009 - Özbek, Melih. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
The Hadronic Forward (HF) calorimeter improves the jet detection and the missing transverse energy resolution of the Compact Muon Solenoid (CMS). In HF, the Photo Multiplier Tubes (PMTs) convert optical signals (i.e., Čerenkov light) to electrical signals. For monitoring the PMT gains, LED signals are extensively used. LED data collected throughout 2009 were thoroughly studied in this thesis. The focus was analyzing the stability of the LED system over time by graphical means. Also, by plotting the average charge versus position, it was possible to identify problematic channels.
Keywords: Particles (Nuclear physics); Particle acceleration.